Is the Affordable Care Act Medicaid Expansion Linked to Change in Rate of Ventricular Assist Device Implantation for Blacks and Whites?. (April 2020) - Breathett, Khadijah K.; Knapp, Shannon M.; Wightman, Patrick; Desai, Archita; Mazimba, Sula; Calhoun, Elizabeth; Sweitzer, Nancy K.
Abstract : Background: The Affordable Care Act (ACA) has been associated with increased heart transplant listings among blacks, who are disproportionately uninsured. It is unclear whether the ACA is also associated with increased ventricular assist device implantation in blacks. Methods: Using Healthcare Cost and Utilization Project Data State Inpatient Databases from 19 states and Washington DC, we analyzed 1157 patients from early-adopter states (ACA Medicaid expansion by January 2014) and 785 patients from nonadopter states (no implementation from 2013 to 2014). Piecewise Poisson regression with a discontinuity was used to estimate change in census-adjusted rates of ventricular assist device implants by race and ACA adopter status 1 year before and after January 2014. Results: Following the ACA Medicaid expansion, the proportional change in rate increased significantly among blacks from early adopter (1.40 [95% CI, 1.12–1.75], pre 0.57/100 000 to post-ACA 0.80/100 000) but not nonadopter states (1.25 [95% CI, 0.98–1.58], pre 0.40/100 000 to post-ACA 0.50/100 000). However, the early and nonadopter changes in implantation rates were not statistically different from each other ( P =0.50). There were no immediate changes in whites in either state group following the ACA Medicaid expansion (early adopter, 1.12 [95% CI, 0.98–1.29], pre 0.27/100 000 to post-ACA 0.30/100 000; nonadopter, 0.98 [95% CI, 0.82–1.16], pre 0.27/100 000 to post-ACA 0.26/100 000). Conclusions: Among eligible states participating in Healthcare Cost and Utilization Project Data State Inpatient Databases, the ACA was not associated with immediate changes in ventricular assist device implantation rates by race. Although a significant increase in implantation rate was observed among blacks from early-adopter states, the change was not statistically different from the change seen in nonadopter states. Abstract : Supplemental Digital Content is available in the text.